2018
DOI: 10.1016/j.diabres.2018.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Lower mortality and cardiovascular event rates in patients with Latent Autoimmune Diabetes In Adults (LADA) as compared with type 2 diabetes and insulin deficient diabetes: A cohort study of 4368 patients

Abstract: LADA seems to be associated with lower mortality and lower risk of cardiovascular events, compared with both T2D and IDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
12
2
1
Order By: Relevance
“…An analysis conducted with 45 LADA patients from a cohort of the Fremantle Diabetes Study found similar crude incidence rates of myocardial infarction, stroke or cardiac mortality to those in T2D patients, again despite the significant differences in CV risk factors . On the contrary, in a recent cohort study LADA seemed to be associated with lower short‐term risk of CV events and mortality, even though patients with insulin‐dependent diabetes were not considered as possibly affected by LADA. Another cross‐sectional study showed that LADA patients had a higher prevalence of carotid atherosclerosis than age‐matched T2D patients .…”
Section: Discussionmentioning
confidence: 75%
“…An analysis conducted with 45 LADA patients from a cohort of the Fremantle Diabetes Study found similar crude incidence rates of myocardial infarction, stroke or cardiac mortality to those in T2D patients, again despite the significant differences in CV risk factors . On the contrary, in a recent cohort study LADA seemed to be associated with lower short‐term risk of CV events and mortality, even though patients with insulin‐dependent diabetes were not considered as possibly affected by LADA. Another cross‐sectional study showed that LADA patients had a higher prevalence of carotid atherosclerosis than age‐matched T2D patients .…”
Section: Discussionmentioning
confidence: 75%
“…However, a post-hoc analysis from UKPDS study showed a lower risk of microvascular complications at diabetes onset in LADA patients comparing to T2DM, followed by a higher risk after 9 years of disease due to worse glycaemic control [23]. In what concerns to cardiovascular disease, it seems to occur at a higher frequency in T2DM, comparing to LADA and T1DM [22,24]. Our study showed a non-statistically signi cant trend to a higher proportion of T1DM patients with macrovascular complications.…”
Section: Metabolic Control and Diabetes Complicationsmentioning
confidence: 99%
“…The FDDB cohort has proven useful in previous publications, and several studies are ongoing 13 19 20. In a cross-sectional study of 4374 adults, measurement of fasting C-peptide and the presence or absence of GAD autoantibodies at first hospital admission with diabetes could be used to define a subgroup of patients with clinically relevant differences in glycaemic control and markers of cardiovascular disease risk (BMI, blood pressure, lipid profile and liver enzymes) 20.…”
Section: Findings To Datementioning
confidence: 99%
“…Based on the literature, the prevalence of diabetic retinopathy was fairly comparable to diabetic patients from cohorts in similar countries, including Sweden21 and Wales,22 supporting that the FDDB comprises a relatively representative sample of patients with diabetes. The FDDB has also been used to study the prognosis related to diabetes 19. Patients with latent autoimmune diabetes in adults (LADA), representing ~10% of patients with type 2 diabetes with circulating islet autoantibodies as seen in type 1 diabetes mellitus, were identified and followed for subsequent mortality and cardiovascular outcomes.…”
Section: Findings To Datementioning
confidence: 99%